If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 4 = -2x + -7 Reorder the terms: 4 + 6x = -2x + -7 Reorder the terms: 4 + 6x = -7 + -2x Solving 4 + 6x = -7 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 4 + 6x + 2x = -7 + -2x + 2x Combine like terms: 6x + 2x = 8x 4 + 8x = -7 + -2x + 2x Combine like terms: -2x + 2x = 0 4 + 8x = -7 + 0 4 + 8x = -7 Add '-4' to each side of the equation. 4 + -4 + 8x = -7 + -4 Combine like terms: 4 + -4 = 0 0 + 8x = -7 + -4 8x = -7 + -4 Combine like terms: -7 + -4 = -11 8x = -11 Divide each side by '8'. x = -1.375 Simplifying x = -1.375
| 6(5-X)=-2(X+43) | | 50m+42975=45450-175m | | b+25=-69 | | 2=5y+2 | | y-3=3/4(x-16) | | y/10=3/6 | | 6/9=y/12 | | log(8x-15)=2 | | 11x(12-x)-30=20x+59-6x(4x-13) | | 1/6+2/3+1/18=n | | 1/6+2/3+1/18= | | 3x-6y=-21 | | 90/95=n/19 | | 0.02/100 | | 12/14=n/7 | | Y^1/3*y^4/3 | | 6(x-2)=9x-3(2x+1) | | X=4y^2-y^3 | | 7x+4y=390 | | 5x-1x=11-3 | | 31=3z+1 | | x-28=8y^2-32y | | x=-2y^2+6y | | 4x-5x+3=14x | | 7cos-1=0 | | 2y+3=25 | | x=2y^2+6y | | -12x^2+4x+6=0 | | (x-4)2+(y-8)2= | | 49-x^2=log(x^2+10x+25) | | 7x-3(x-2)=2(2-c) | | 180=7x+5x |